A massive terraced village complex in Chihuahua, Mexico, 3000 years before present - Hard, R. J.; Roney, J. R. (Science, 1998)
Cerro Juanaquena is a residential complex with 8 kilometers of terrace walls in northwestern Mexico that was occupied at similar to 3000 calendar years before present based on radiocarbon dates on maize (Zea mays L.), Most other similar sized terrace complex sites that have been found date to similar to 1000 years before present, Cerro Juanaquena was contemporaneous with 10 other sites in the southwestern United States that have yielded 18 of the earliest maize or squash radiocarbon dates yet, and it is by far the largest and most complex site, The archaeological evidence from this site, combined with other recent data, implies that highly variable combinations of population aggregation, agricultural dependence, and degrees of sedentism were present during the time maize was being introduced into the American Southwest.
Zb612Times Cited:32Cited References Count:59